Relationship of sarcopenia with steatohepatitis and advanced liver fibrosis in non-alcoholic fatty liver disease: a meta-analysis - Rui Yu; Qiangwei Shi; Lei Liu; Lidong Chen (BMC Gastroenterology, 2018)
Abstract Background Several studies have emerged indicating that sarcopenia is associated with nonalcoholic fatty liver disease, we aimed to systematically review and quantify the association between sacropenia and the histological severity of nonalcoholic fatty liver disease. Methods Pubmed, the Cochrane Library and EMBASE were searched (until August 2017) for studies examining the relationship of sarcopenia with steatohepatitis and advanced liver fibrosis in nonalcoholic fatty liver disease. Pooled odds ratios were estimated by fixed effects models. Results Three articles met our inclusion criteria, with a total of 3226 individuals. Two of the studies examined the association between sacropenia and steatohepatitis, a significant association was documented between sarcopenia and steatohepatitis (OR = 2.35, 95%CI 1.45, 3.81). All of the three studies assessed the association between sacropenia and advanced liver fibrosis, a significant association between sarcopenia and advanced liver fibrosis (OR = 2.41, 95%CI 1.94, 2.98). No significant heterogeneity was detected among studies in all comparisons. These results remained essentially unchanged after excluding any of the studies in the sensitivity analysis. Conclusions Sarcopenia in patients with nonalcoholic fatty liver disease is associated with a higher likelihood of having steatohepatitis or advanced liver fibrosis. Demonstration of the role of sarcopenia in nonalcoholic fatty liver disease development in future studies could have important therapeutic implications.